Recovery of the breast screening programme following pandemic-related delays: Should we focus on round length or uptake?. (June 2022) - Duffy, Stephen W.; Hudson, Sue; Vulkan, Daniel; Duffy, Thomas E.; Binysh, Kathie
Objectives: The NHS Breast Screening programme is recovering from the hiatus in screening in 2020 due to the COVID-19 pandemic. Currently, open rather than timed invitations are issued, which leads to lower uptake but more rapid coverage of the eligible population by invitation and therefore closer adherence to a round length of 3 years. We aimed to estimate the likely effect on numbers of cancers detected at incident screens of a range of round lengths and uptake rates. Methods: We assumed exponential distributions of time to incidence of preclinical screen-detectable cancer and of time to progression thereafter to symptomatic clinical disease. We derived numerical values of these, along with screening sensitivity, from published research results and statistics from the NHS Breast Screening programme. These were used to calculate numbers of cancers detected at incident screens at ages 51–70 by round length and uptake rates. Results: We found that in a homogeneous population of cancers, a 4-year round length with uptake of 62%, as observed with timed appointments in London before the pandemic, would result in 295 cancers screen detected per 10, 000 invited, compared to 222 cancers with a 3-year round and uptake of 46%, as observed in London during the recovery period. Similar results were found when we posited two populations, one of rapidly progressing and one of slowly progressing cancers. Conclusions: It may be more productive in terms of early detection to focus on uptake rather than round length in the programme's recovery from the pandemic.